Cholinesterases as markers of the inflammatory process associated oxidative stress in cattle infected by Babesia bigemina - Doyle R.L. (2016)
© 2016 .The objective of this study was to assess the influence of an asymptomatic experimental infection by Babesia bigemina on cholinesterase's as markers of the inflammatory process and biomarkers of oxidative imbalance. For this purpose, eight naive animals were used, as follows: four as controls or uninfected; and four infected with an attenuated strain of B. bigemina. Blood samples were collected on days 0, 7 and 11 post-inoculation (PI). Parasitemia was determined by blood smear evaluation, showing that the infection by B. bigemina resulted in mean 0.725 and 0.025% on day 7 and 11 PI, respectively, as well as mild anemia. The activities of acetylcholinesterase, butyrylcholinesterase and catalase were lower, while levels of thiobarbituric acid reactive substances and superoxide dismutase activity were higher in infected animals, when compared with the control group. This attenuated strain of B. bigemina induced an oxidative stress condition, as well as it reduces the cholinesterasés activity in infected and asymptomatic cattle. Therefore, this decrease of cholinesterase in infection by B. bigemina purpose is to inhibit inflammation, for thereby increasing acetylcholine levels, potent anti-inflammatory molecules.